PENGARUH REINVENTING POLICY, SIKAP RASIONAL, DAN KEADILAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA MANADO - Purba, Irene Catrine; Ilat, Ventje; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Taxpayer compliance is an attitude of obedience in carrying out the provisions and regulations required taxation and must be done by taxpayer. Taxpayer compliance may be influenced by the reinventing policy, rational attitude, and tax fairness. The population in this research individual taxpayer in KPP Pratama Manado. The sample in this research is 50 respondents with using incidental sampling technique. This research method is a type of a survey research, is research conducted by using a questionnaire as a research tool. The analyzes technique used is multiple linear regression and by using software SPSS. The results show the reinventing policy (Xâ) have a negative effect on the taxpayer compliance. Rational attitude (Xâ) have an effect on the taxpayer compliance (Y). Tax fairness (Xâ) has no effect on the taxpayer compliance (Y).Keywords: reinventing policy, rational attitude, tax fairness, tax compliance